1993
DOI: 10.1037/h0080288
|View full text |Cite
|
Sign up to set email alerts
|

Stability and determinants of psychosocial well-being in multiple sclerosis.

Abstract: Illness intrusiveness -illness-induced life style disruptions -was hypothesized to compromise psychosocial well-being in multiple sclerosis (MS) by (a) interfering with continued involvements in valued activities and interests and (b)decreasing personal control over important life domains. Three categories of illnessrelated variables were hypothesized to contribute to increased illness intrusiveness: burden of illness (i.e., direct physical action and effects of disease), functional deficits (i.e., operational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
37
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(40 citation statements)
references
References 40 publications
2
37
1
Order By: Relevance
“…For example, a recent study of veterans found that perceived mobility and bladder impairment were not associated with increased risk of depression but reports of perceived bowel impairment and "at least occasional" falls were associated with elevated risk of depression [19]. A possible explanation for these findings comes from Devins et al who found that the relationship between physical disability and depression is indirect: disability affects psychosocial outcome to the degree that impairment is intrusive and personal control is threatened [20].…”
Section: Physical and Cognitive Impairmentmentioning
confidence: 91%
“…For example, a recent study of veterans found that perceived mobility and bladder impairment were not associated with increased risk of depression but reports of perceived bowel impairment and "at least occasional" falls were associated with elevated risk of depression [19]. A possible explanation for these findings comes from Devins et al who found that the relationship between physical disability and depression is indirect: disability affects psychosocial outcome to the degree that impairment is intrusive and personal control is threatened [20].…”
Section: Physical and Cognitive Impairmentmentioning
confidence: 91%
“…A carer is someone who provides a significant amount of voluntary unpaid support and help to a friend, relative, or a neighbour, who suffers from an illness, disability, frailty, mental health problem, or addiction (Carers Trust, 2012;Carers UK, 2015; Department of Health [DoH], 2014). The word 'informal' is commonly used to distinguish voluntary unpaid carers from health professionals or care workers who get paid for providing care.As a result of the progressive, unstable and unpredictable nature of MS, caring for pwMS causes high levels of carer burden and is recognised as a potential threat to caregivers' health and well-being (Corry & While, 2009;Devins, Seland, Klein, Edworthy, & Saary, 1993). Indeed, there is consistent evidence in the current literature that overall quality of life (QoL) is low among informal carers of pwMS (see Corry & While, 2009).…”
mentioning
confidence: 84%
“…As a result of the progressive, unstable and unpredictable nature of MS, caring for pwMS causes high levels of carer burden and is recognised as a potential threat to caregivers' health and well-being (Corry & While, 2009;Devins, Seland, Klein, Edworthy, & Saary, 1993). Indeed, there is consistent evidence in the current literature that overall quality of life (QoL) is low among informal carers of pwMS (see Corry & While, 2009).…”
mentioning
confidence: 84%
“…Mixed findings such as these suggest the presence of moderators. Regarding effect sizes, four studies reported moderate effect sizes (McIvor et al, 1984;Mohr et al, 1997;Pujol et al, 2000;Zorzon et al, 2001), one large (Kneebone & Dunmore, 2004) and another small , with two studies reporting both small and moderate effect sizes (Devins et al, 1993;Lynch et al, 2001). Due to the way the data were presented, it was not possible to estimate effect sizes for three studies but the findings they reported were statistically significant (Chwastiak et al, 2002;Goodin & the Northern California MS Study Group, 1999;Janssens et al, 2003).…”
Section: Depression In Ms 693mentioning
confidence: 99%